Release of VEGF and BMP9 from injectable alginate based composite hydrogel for treatment of myocardial infarction - Wu, Yong (Bioact Mater, 2020)
Myocardial infarction (MI) is one of cardiovascular diseases that pose a serious threat to human health. The pathophysiology of MI is complex and contains several sequential phases including blockage of a coronary artery, necrosis of myocardial cells, inflammation, and myocardial fibrosis. Aiming at the treatment of different stages of MI, in this work, an injectable alginate based composite hydrogel is developed to load vascular endothelial active factor (VEGF) and silk fibroin (SF) microspheres containing bone morphogenetic protein 9 (BMP9) for releasing VEGF and BMP9 to realize their respective functions. The results of in vitro experiments indicate a rapid initial release of VEGF during the first few days and a relatively slow and sustained release of BMP9 for days, facilitating the formation of blood vessels in the early stage and inhibiting myocardial fibrosis in the long-term stage, respectively. Intramyocardial injection of such composite hydrogel into the infarct border zone of mice MI model via multiple points promotes angiogenesis and reduces the infarction size. Taken together, these results indicate that the dual-release of VEGF and BMP9 from the composite hydrogel results in a collaborative effect on the treatment of MI and improvement of heart function, showing a promising potential for cardiac clinical application.